Age, Sex, and Seasonal Variations in the Serum Vitamin D3 Levels in a Local Turkish Population - Sinem BOZKURT; Berat Meryem ALKAN; Fatma YILDIZ; Sevgi GÜMÜŞ; Nebahat SEZER; 2 Özge ARDIÇOĞLU; Selami AKKUŞ2 (Archives of Rheumatology, 2014)
Objectives: This study aims to assess the 25-hydroxyvitamin D [25-(OH)D] levels in patients who were seen at a physical medicine and rehabilitation outpatient clinic while also taking into account the seasonal serum vitamin D (vit D) variation. Patients and methods: We retrospectively evaluated the medical records of the patients who attended a physical medicine and rehabilitation outpatient clinic, and the serum 25-(OH)D levels in 440 subjects of varying ages and sexes in both the summer (n=177) and winter (n=263). Serum 25-(OH)D, parathyroid hormone, alkaline phosphatase (ALP), calcium, and phosphorus levels were recorded. Results: A large percentage of the adult Turkish population has insufficient levels of vit D during the winter and summer. Serum 25-(OH)D levels were significantly lower in the winter compared with the summer season (mean vit D: 13.9 μ/l and 19.7 μ/l, respectively; p≤0.001). The prevalence of 25-(OH)D deficiency was 94% in the winter and 85% in the summer. With respect to age or sex, there were no differences in the 25-(OH)D levels. Conclusion: Our results indicate that although Turkey is a Mediterranean country, the Turkish people should check have their levels of 25-(OH)D periodically checked, and if necessary, appropriate supplements should be given to prevent a secondary chronic disease due to vit D deficiency.